2004
DOI: 10.1016/j.foodchem.2004.01.055
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic profile in the quality control of walnut (Juglans regia L.) leaves

Abstract: Qualitative and quantitative determinations of phenolic compounds were carried out on walnut leaves samples from six different cultivars, with the same agricultural, geographical and climatic conditions. The evolution of major phenolic compounds amounts was monitored from May to September. Two extractive procedures were assayed and best results were obtained using acidified water and a solid phase extraction column purification step. Qualitative analysis was performed by HPLC-DAD/MS and, in all samples, seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(119 citation statements)
references
References 13 publications
8
109
1
1
Order By: Relevance
“…In accordance with literature Amaral et al, 2004), juglone was identified in all cultivars, but there were differences among cultivars regarding content and between materials showed. In general juglone content is higher in green husk of walnut fruits.…”
Section: Discussionsupporting
confidence: 89%
“…In accordance with literature Amaral et al, 2004), juglone was identified in all cultivars, but there were differences among cultivars regarding content and between materials showed. In general juglone content is higher in green husk of walnut fruits.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, because of polymerization phenomena, juglone only occurs in dry leaves at vestigial amounts (Wichtl & Anton, 1999). Several hydroxycinnamic acids (3-caffeoylquinic, 3-p-coumaroylquinic and 4-p-coumaroylquinic acids) and flavonoids (quercetin 3-galactoside, quercetin 3-arabinoside, quercetin 3-xyloside, quercetin 3-rhamnoside and two other partially identified quercetin 3-pentoside and kaempferol 3-pentoside derivatives) of different walnut cultivars collected at different times were detected (Amaral et al, 2004). In addition, the existence of 5-caffeoylquinic acid was also reported (Wichtl & Anton, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Amaral et al (2004) determined the phenolic profile of walnut leaves of several cultivars. This variety was characterized by the presence of at least nine phenolic compounds: three hydroxycinnamic acid derivatives, the 3-O-caffeoylquinic, 3-O-p-coumaroylquinic and 4-O-p-coumaroylquinic acids, and six flavonol heterosides, the quercetin 3-O-galactoside (its major compound), a quercetin 3-O-pentoside derivative, quercetin 3-O-arabinoside, quercetin 3-Oxyloside, quercetin 3-O-ramnoside and a kaempferol 3-Opentoside (Amaral et al, 2004). Pereira et al (2007) identified another two hydroxycinnamic acid derivatives, the 5-Ocaffeoylquinic and p-coumaric acids.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic acids and flavanoids, two main groups of compounds in walnut leaf extract (Amaral et al, 2004), have been the subject of several studied due to their antioxidant potential and their capability of free radical scavenging (Pereira et al, 2007). In total flavonoid determination, we used quercetin as a standard compound because it is one of the widely spread flavonoids in walnut leaves extract (Amaral were irradiated by microwaves (1000 W, Butan, Iran) as the follows: 2 min 10% full power on (heating to the desired temperature, lower than 40℃ and 3 min power off and then 1 min 10% full power on (for heating) and 3 min power off (for cooling) and so on to the pre-set extraction time (4 min).…”
Section: Resultsmentioning
confidence: 99%